Construction of a femtosecond laser for the study of aberrations in optical systems - González Galicia, Miguel Ángel; Rosete-Aguilar, M.; C. Bruce, N.; Garduño-Mejía, J.; Ortega-Martínez, R. (Acta Universitaria, 2013)
We present the construction of a femtosecond laser, based on a titanium sapphire crystal. This laser produce pulses of 20 fs. We also present theoretical results for the electric field distribution near the focal plane of a lens for gaussian illumination under the influence of primary aberrations: spherical aberrations, coma, astigmatism and field curvature, for an achromatic doublet. The theoretical results are compared with results obtained with the laser system constructed.
Keywords: Array; Array; Array; Array; Array; Array; Array